“If I could try it, I’d try it”: Qualitative study of the illegal vaping culture in Singapore - Grace Ping Ping Tan; Xian Zhen Tan; Yvette van der Eijk (Addictive Behaviors Reports)
Aims and background: Singapore has one the world’s strictest e-cigarette (vaping) regulations, with bans on e-cigarette import, sale, purchase, use and possession. Nevertheless, Singapore is seeing a growing vaping trend. Beyond estimates of vaping prevalence, little is known about vaping in countries where it is banned or the features and drivers of such illegal vaping cultures. This qualitative study thus explored the characteristics of Singapore’s illegal vaping culture. Methods: We held ten focus group discussions with 63 Singaporeans aged 21–40 years, exploring participants’ experiences and views related to vaping in Singapore. Transcripts of the discussions were coded using deductive and inductive coding methods. Results: Despite its illegal status, vaping was perceived as appealing due to the novelty flavours, ease of use, and convenient access. Harm perceptions were mixed, with concerns over the adverse health impacts along with beliefs that vaping was innocuous when used in moderation. A conspicuous vaping culture among young people, along with perceptions of lax enforcement, drove beliefs that vaping is an entrenched social norm in Singapore. This belief was in turn associated with a sentiment that Singapore should introduce a regulated e-cigarette market to better control its use among the general population. Conclusions: The reinforcement of vaping as a social norm appears to be driving an illegal vaping culture in Singapore. Measures that denormalise vaping could help to strengthen the effectiveness of the vaping ban.